KAJIAN MINUS ONE TEST DAN KESUBURAN LAHAN PASIR UNTUK BUDIDAYA TANAMAN BAWANG MERAH - nFN Sutardi (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
Soil Fertilyty and Minus One Test of Sandy Land For Shallot. Besides to prove the potential of N, P and K nutrients as limiting factors for shallot plants, the objectives of this research was to find out physical characteristics and fertility in sandy land (soils) in Bantul, Kulon Progo district, Special Region of Yogyakarta. Research was carried out in two stages. The first stage was survey and analysis of sandy land in Bantul and Kulon Progo by the age ofamelioration. Survey techniques was based on four age ameliorations of sandy soil. The second stage was conducted using complete randomized block design sigle factor. The second was minus one test of N, P and K consists of five treatments: 1 .TP = no fertilizer (control), 2. PK (-N) = complete fertilizer without N, 3. NK (-P) = complete fertilizerwithout P, 4.NP (-K) = complete fertilizer without K and 5. NPK = complete fertilizer. The results showed that the introduction of amelioration techniques changed and improved soil different changes in physical and chemical of sandy land. Ameliorant addition into the planting media had positive with the percentage change in silt (0.55-2.37%) and clay (0.45-0.51%) increasing significantly, followed by levels P2O5 and lowerring the sand (1.05-2.07%). The result of minus one test fertilizer on sandy land for the shallot that fertilizer N become the main limiting factor P and K light whereas P and K nutrients were the limiting factor on sandy land for shallot. Ameliorant, sandy land, shallotABSTRAKTujuan penelitian untuk membuktikan bahwa hara N, P, dan K faktor pembatas untuk pertumbuhan dan produksi bawang merah pada lahan pasir pantai. Disamping itu juga mengetahui perubahan sifat fisik dan kimia tanah lahan pasir pantai pada berbagai blok dengan umur penggunaan lahan yang berbeda. Penelitian dilakukan dua tahap yaitu pertama survei dan analisis tanah lahan pasir di Kabupaten Bantul dan Kulon Progo D.I. Yogyakarta berdasarkan umur ameliorasi. Penelitian kedua mengetahui faktor pembatas menggunakan Rancangan Acak Kelompok Lengkap (RAKL) faktor tunggal. Perlakuan minus one test hara N, P dan K terdiri dari lima perlakuan: 1. TP = tanpa pupuk(kontrol), 2. PK (-N) = pupuk lengkap kurang N, 3. NK (-P) = pupuk lengkap kurang P, 4. NP (-K) pupuk lengkap kurang K dan 5. NPK pupuk lengkap diulang 5 kali. Hasil kajian menunjukkan bahwa pengelolaan lahan pasir dengan input bahan amelioran terjadi perubahan sifat fisik dan kimia sehingga kesuburan lahan meningkat. Peningkatantersebut karena terjadi perubahan persentase fraksi debu (0,55-2,37%) dan (0,45-0,51%) liat meningkat diikuti kadar hara P2O5, menurunkan fraksi pasir (1,05-2,07%) secara nyata. Hara N menjadi faktor pembatas utama, sedangkan K dan P merupakan pembatas ringan pada lahan pasir untuk bawang merah.Amelioran, lahan pasir, bawang merah